2013
DOI: 10.12705/624.34
|View full text |Cite
|
Sign up to set email alerts
|

Calla palustris (Araceae): New palynological insights with special regard to its controversial systematic position and to closely related genera

Abstract: Almost all systematic treatments agree that is a puzzling case, being a highly autapomorphic taxon with obscure relationships. In molecular-based classifications the variable placements of within Aroideae conflict strongly with those in morphologically and anatomically based systematic classifications, which treat the genus as a subfamily (Calloideae) of its own. We studied the pollen morphology and ultrastructure of by light and electron microscopy, and mapped the relevant pollen characters as well as some fl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
9
0
1

Year Published

2013
2013
2023
2023

Publication Types

Select...
6
2

Relationship

2
6

Authors

Journals

citations
Cited by 10 publications
(10 citation statements)
references
References 26 publications
0
9
0
1
Order By: Relevance
“…), and Nephthytis (2 spp. ), and the species Calla palustris was sequenced twice (because of its unexpected systematic placement; Ulrich et al 2013).…”
Section: Molecular Phylogeneticsmentioning
confidence: 99%
“…), and Nephthytis (2 spp. ), and the species Calla palustris was sequenced twice (because of its unexpected systematic placement; Ulrich et al 2013).…”
Section: Molecular Phylogeneticsmentioning
confidence: 99%
“…2H). Its cylindrical spadix comprises white, bisexual flowers (Lehman & Sattler, 1992;Ulrich et al, 2013) and at the top a group of flowers with exclusively nonfunctional stamens (Chartier et al, 2017).…”
Section: Callamentioning
confidence: 99%
“…Some subfamilies, like Pothoideae, encompass species-rich genera, such as Anthurium Schott, whereas others, e.g., Gymnostachydoideae, are monotypic (Mayo et al, 1997). These plants (including the monotypic genus Calla L., possibly included in Aroideae or sister to it, but whose position remains uncertain; see Ulrich et al, 2013;Chartier et al, 2014) encompass 31 genera and about 1500 species (Mayo et al, 1997;Boyce & Croat, 2018). In contrast to taxa with unisexual flowers, their pollination mechanisms are still poorly understood (Mayo et al, 1997;Hentrich et al, 2010).…”
mentioning
confidence: 99%
“…On the other hand, the unisexual clade is itself unsupported in the most comprehensive analyses so far published (Cabrera et al, 2008;Cusimano et al, 2011;Nauheimer et al, 2012;Chartier et al, 2014). Further ambiguity is provided by the genus Calla, which combines bisexual flowers and pollen structure more typical of bisexual-flowered genera (Ulrich et al, 2013), but which is consistently placed within the unisexual clade by molecular analyses and in very variable positions (Figure 1). The potential of phylogenomic tools to provide new evidence on the floral sexuality transition first began to be demonstrated in an analysis by Henriquez et al (2014), who studied whole plastid genomes of 37 genera and found full support for the unisexual clade, placing Calla well within it and at a position comparable to the finding of Cusimano et al (2011).…”
mentioning
confidence: 99%